Beyond managing work and non-work demands: The role of organizational work-life initiatives on work-life interaction and job satisfaction - Pujol-Cols, Lucas (2025)
Over the past decades, the changing nature of gender roles, families, work, and careers has spurred scholarly interest in work-life interaction. These changes have posed challenges for employees in managing work and non-work demands in increasingly complex scenarios, as well as for organizations, which are expected to provide resources—known as organizational work-life initiatives—to help employees meet both responsibilities effectively. While much research on work-life interaction has focused on work-life conflict and its negative effects on job performance, family, and life satisfaction; scholars have also highlighted the significance of work-life enrichment resulting from the positive dynamics between work and personal life. Despite their interconnected nature, work-life  conflict and work-life enrichment are often studied in isolation, limiting the understanding of the broader dynamics of work-life interaction. This study examines the role of organizational work-life initiatives in the relationship between work-life interaction and job satisfaction using a non-random sample of 362 Argentinian employees. Regression analysis reveals that initiatives, particularly those related to job flexibility, are essential in mitigating work-life conflict and promoting work-life enrichment. These findings  contribute to the literature by offering a more comprehensive understanding of how organizational worklife initiatives influence employees’ affective responses to work-life interaction.